PELAKSANAAN LELANG TERHADAP KREDIT MACET PADA PT. BANK RAKYAT INDONESIA (PERSERO) CABANG DUMAI - Ariyana Rezki Ananda; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Bank according to Article 1 paragraph 2 of Law No. 10 of 1998 concerning Amendment to Law Number 7 of 1992 concerning Banking,